2016
DOI: 10.4103/0973-1482.154939
|View full text |Cite
|
Sign up to set email alerts
|

Electronic game: A key effective technology to promote behavioral change in cancer patients

Abstract: Cancer diagnosis is a very unpleasant and unbelievable experience. Appropriate management and treatment of these diseases require a high degree of patient engagement. Interactive health electronic games are engaging, fun, challenging, and experiential and have the potential to change the attitude and behavior, which can improve the player's health. The use of these digital tools, as one of the most attractive and entertaining modern technologies, canem power patients, provide suitable palliative care, promote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Applications of game-based learning in professional and academic settings are beginning to appear in scholarly publications. Scholarly evidence related to healthcare interventions for adolescents and young adults exists demonstrating behavioral change through game-based learning (Baranowski et al, 2015;Baranowski, Buday, Thompson, & Baranowski, 2008;Kato, Cole, Bradlyn, & Pollock, 2008;Safdari, Ghazisaeidi, Goodini, Mirzaee, & Farzi, 2016). The social nature of play and the networking availability inherent to modern mobile social platforms have broadened the market for, and acceptance of serious games with the potential to drive behavioral change (Gee, 2003;McCallum, 2012;Squire, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Applications of game-based learning in professional and academic settings are beginning to appear in scholarly publications. Scholarly evidence related to healthcare interventions for adolescents and young adults exists demonstrating behavioral change through game-based learning (Baranowski et al, 2015;Baranowski, Buday, Thompson, & Baranowski, 2008;Kato, Cole, Bradlyn, & Pollock, 2008;Safdari, Ghazisaeidi, Goodini, Mirzaee, & Farzi, 2016). The social nature of play and the networking availability inherent to modern mobile social platforms have broadened the market for, and acceptance of serious games with the potential to drive behavioral change (Gee, 2003;McCallum, 2012;Squire, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Some of these diseases are rare, and these symptoms will stop a short time after the person leaves the computer game, but others are produced because of overuse and addiction to this game. [3738]…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that serious games support the player's learning by providing interactivity, being interesting and immersive with in-game reward opportunities, enabling discovery by guiding the player, and being a method of knowledge transfer (Pourabdollahian et al, 2012). In addition, it is pointed out that using games would have beneficial effects such as providing education without time and place restrictions, increasing patient satisfaction, improving health behaviors by educating the society, promoting health culture, increasing motivation, reducing the negative physical and psychological consequences of the disease, ensuring lifestyle change and maintaining well-being (Safdari et al, 2016).…”
Section: Introductionmentioning
confidence: 99%